Corrosion Characteristics of Copper in Malaysian Bioethanol and Gasoline blends - Saravana, Kannan Thangavelu; Piraiarasi, C.; Abu Saleh, Ahmed; Ani, F.N. (Trans Tech Publications, Switzerland, 2014)
The present study aims to investigate the corrosion characteristics of copper commonly encountered in the spark ignition (SI) engine fuel system with Malaysian bioethanol and gasoline blends. Static immersion tests in E0 (gasoline), E10 and E85 were carried out at room temperature for 1320 h. Mechanical, physical and chemical properties of copper was investigated before and after immersion tests. Investigations were carried out on change in morphological properties using optical microscope; change in chemical structure using FTIR; change in mass and volume by weight loss measurement; hardness changes using universal hardness tester; and change of chemical properties of the fuel blends using total acid number titration method. The test results showed that corrosion of copper was increased with the high concentration of ethanol in the blends.